Cycled hydrogen permeation through Armco iron – A joint experimental and modeling approach. (November 2020) - Drexler, A.; Siegl, W.; Ecker, W.; Tkadletz, M.; Klösch, G.; Schnideritsch, H.; Mori, G.; Svoboda, J.; Fischer, F.D.
Graphical abstract: Highlights: Cycled permeation experiments are evaluated with physically sound diffusion models. Use of Armco iron eliminates the role of defects due to alloying and precipitation. Hydrogen trap sites are identified and their densities and energies are determined. Fully parametrized diffusion and trapping model is provided. Microstructure-property relations for trap density evolution are presented. Abstract: Understanding hydrogen embrittlement in steels requires research in hydrogen diffusion and trapping at microstructural defects. The present paper deals with hydrogen permeation and trapping at defects in the base material, Armco iron, eliminating effects coupled with alloying and precipitation. Cycled permeation curves are recorded and evaluated by using sound diffusion models to identify hydrogen trap sites as dislocations, grain boundaries and vacancies and assign their trapping energies. Furthermore, trap densities are evaluated and used together with the trapping energies as parameters in an adapted diffusion equation for hydrogen, interpreting the experiments significantly better than simple use of classical Fick's laws.